Amplitude analysis of the radiative decay B0s → K+K-γ - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2024)
A search for radiative decay of mesons to orbitally excited K+K− states is performed using proton proton collisions recorded by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1. The dikaon spectrum in the mass range mKK < 2400 MeV/c2 is dominated by the ϕ(1020) resonance that accounts for almost 70% of the decay rate.